The internationalization of higher education in Argentina (1995 – 2015): global convergence or national peculiarities? - Botto, Mercedes (2017)
The objective of this essay is to analyse the influence of international agencies in the process of internationalization of higher education system in Argentine. The interest of this analysis is two-fold: on the one hand contribute to the debate on the effects of convergence/divergence resulting from economic globalization on national public policy. On the other hand, to characterize the path of reform followed by a case, the Argentine, who was distinguished from its origins by its massiveness, the autonomy of universities and its public funding: three elements that would go against the grain of the hegemonic ideas of the 1990s. What were these ideas and hegemonic proposals? To what extent they managed to modify and change these pillars? Which exogenous actors were committed to propose these reforms and which domestic actors supported and benefited with them?. To answer these questions, this paper characterizes the major milestones of this reform by identifying the actors, ideas, and resources used by international actors and the responses generated by their domestic counterparts. Qualitative Data came from official documents and academic publications that were checked in some cases interviews with its protagonists. The results allow us to speak of three distinct and successive but largely complementary stages. Each of these stages is characterized by the presence of an international body whose ideas have influenced the reform of the national system. However this influence was not direct, but mediated by the views and interests of domestic actors.